Mitochondrial DNA and Disease: Areview - Adel Hussein, Marwa; Hameed Abdulridha, Ruaa; Jasim Sodani, Ibtisam; Adnan Al-Ward, Mais; Ridha Jaafar, May; Khalid Ibrahim Al-Sammarrie, Hala; Emad Neamah, Shahad; A. Jawad, Asmaa; Hussen Safir, Nadhum (Al-Nahrain Journal of Science, 2024)
Mitochondria are organelles responsible for converting energy into a usable form for cellular metabolic activities. These organelles have their own DNA. Mutations in mitochondrial DNA (mtDNA) are frequent despite Its limited number of genes. Molecular genetics diagnostics enables the examination of DNA in many fields, like infectiology, cancer, and genetics of people. It is essential to identify abnormalities in mitochondrial DNA in patients since these mutations directly affect mitochondrial metabolism and may contribute to various illnesses. The mtDNA found in every human cell is a limited and significant source of harmful mutations and rearrangements. This review provides a concise overview of the unique principles of mitochondrial genetics, including maternal inheritance, mitotic segregation, heteroplasmy, and the threshold effect. It emphasizes the relatively common occurrence of medical conditions associated with mitochondrial DNA (mtDNA) and discusses recent discoveries of pathogenic mutations, with a particular focus on mutations that impact protein-coding genes. Next, we go into more contentious topics, such as the functional or pathological significance of mtDNA haplotypes, the disease-causing potential of homoplasmic mutations, and the mostly unknown mechanisms behind mtDNA mutations.